Long-Lasting Orientation of Symmetric-Top Molecules Excited by Two-Color Femtosecond Pulses - Xu, Long; Tutunnikov, Ilia; Prior, Yehiam; Averbukh, Ilya Sh. (Frontiers in Physics, 2021)
Impulsive orientation of symmetric-top molecules excited by two-color femtosecond pulses is considered. In addition to the well-known transient orientation appearing immediately after the pulse and then reemerging periodically due to quantum revivals, we report the phenomenon of field-free long-lasting orientation. Long-lasting means that the time averaged orientation remains non-zero until destroyed by other physical effects, e.g. intermolecular collisions. The effect is caused by the combined action of the field-polarizability and field-hyperpolarizability interactions. The dependence of degree of long-lasting orientation on temperature and pulse's parameters is considered. The effect can be measured by means of second (or higher-order) harmonic generation, and may be used to control the deflection of molecules traveling through inhomogeneous electrostatic fields.